2016
DOI: 10.1093/gbe/evw039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analyses of theMoraxella catarrhalisSerosensitive and Seroresistant Lineages Demonstrate Their Independent Evolution

Abstract: The bacterial species Moraxella catarrhalis has been hypothesized as being composed of two distinct lineages (referred to as the seroresistant [SR] and serosensitive [SS]) with separate evolutionary histories based on several molecular typing methods, whereas 16S ribotyping has suggested an additional split within the SS lineage. Previously, we characterized whole-genome sequences of 12 SR-lineage isolates, which revealed a relatively small supragenome when compared with other opportunistic nasopharyngeal path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…This species is thought to be composed of two distinct lineages, namely the more pathogenic sero-resistant (SR) strains and the less pathogenic sero-sensitive (SS) ones 7 , 8 . These two groups of strains show separate evolutionary histories and contain a distinct subset of lineage-specific genes, 33 and 49, respectively 9 . Some of the genes unique to the SR lineage are involved in phosphate metabolism but others do not have assigned functions.…”
Section: Introductionmentioning
confidence: 99%
“…This species is thought to be composed of two distinct lineages, namely the more pathogenic sero-resistant (SR) strains and the less pathogenic sero-sensitive (SS) ones 7 , 8 . These two groups of strains show separate evolutionary histories and contain a distinct subset of lineage-specific genes, 33 and 49, respectively 9 . Some of the genes unique to the SR lineage are involved in phosphate metabolism but others do not have assigned functions.…”
Section: Introductionmentioning
confidence: 99%
“…1 ), and although currently classified as M. catarrhalis , are predicted to represent a different species or subspecies ( Wirth et al. 2007 ; Earl et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…2017 ). Comparative supragenome analysis of thirteen RB1 and eighteen RB2/3 genomes demonstrated that virulence factors responsible for adherence and serum resistance are found in the core M. catarrhalis genome, with no virulence factors found solely in either lineage ( Earl et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 3 remaining strains identified as M. catarrhalis showed lower homologies. These strains are variant strains and, based on genome sequences, will soon be reclassified as a different species (44).…”
Section: Resultsmentioning
confidence: 99%